OPTIMIZING 3D PRINTING PARAMETERS TO IMPROVE HARDNESS AND SURFACE ROUGHNESS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The purpose of this paper is to study the factors affecting roughness and hardness of 3D printed models. Two parameters are analyzed- 3D printing speed and layer thickness. The main disadvantage of 3D printed models is their higher roughness, which depends on the printing parameters. In order to obtain parts with smoother surfaces, it is necessary to study these parameters. Based on the obtained experimental results, a regression dependence was built describing the relationship between roughness and hardness with the investigated printing parameters.